2020
DOI: 10.1002/ecs2.3077
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of soil organic carbon in a karst region under different land use patterns

Abstract: Citation: Zhang, Z., X. Huang, and Y. Zhou. 2020. Spatial heterogeneity of soil organic carbon in a karst region under different land use patterns. Ecosphere 11(3):Abstract. Using the grid-based sampling method, 2755 soil profiles consisting of 22,057 soil samples were sampled and analyzed to study the spatial distribution and storage of soil organic carbon (SOC) in the Houzhai River Basin in Guizhou Province, a typical karst region in southwestern China. The results suggest that the total levels of SOC stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
2
10
1
Order By: Relevance
“…Different lowercase letters at same stage (days) of decomposition (x-axis) indicate significant differences between treatments (P < 0.05); Soil nutrients are an important indicator for evaluating an adequate nutrient supply belowground. In this study, soil initial C averaged 35 g/kg, considerably lower than the average level of karst forests 45 g/kg, (Zhang et al 2020). The mean soil N was 2 g/kg, which is lower than the average 3 g/kg of karst soil in Guangxi (Chen et al 2012), a disparity explainable by parent material and land reclamation.…”
Section: Correlations Of Ecological Stoichiometry Between Leaf Litter and Soilscontrasting
confidence: 54%
“…Different lowercase letters at same stage (days) of decomposition (x-axis) indicate significant differences between treatments (P < 0.05); Soil nutrients are an important indicator for evaluating an adequate nutrient supply belowground. In this study, soil initial C averaged 35 g/kg, considerably lower than the average level of karst forests 45 g/kg, (Zhang et al 2020). The mean soil N was 2 g/kg, which is lower than the average 3 g/kg of karst soil in Guangxi (Chen et al 2012), a disparity explainable by parent material and land reclamation.…”
Section: Correlations Of Ecological Stoichiometry Between Leaf Litter and Soilscontrasting
confidence: 54%
“…In the intermediate forest stage, the net productivity of the stand increases markedly, biomass accumulates greatly, litter return decreases, and high amounts of soil nutrients are absorbed with low nutrient return to the soil, resulting in a decrease in the contents of soil carbon and nitrogen. In the mature forest, the soil carbon and nitrogen contents exhibited an increasing trend due to the decreased growth rate of the trees, the low tree density, limited litter return, and relatively low absorption and return of soil nutrients that are conducive to the accumulation of soil nutrients in forests [47,48].…”
Section: Effect Of Forest Age On Soil Chemical Propertiesmentioning
confidence: 99%
“…The conservation, migration and distribution of SOM are complex physical, chemical and biological processes affected by many factors. The past literature has shown that because of the variation in soil erosion, the SOM content varies in different regions [7][8][9][10], land-use patterns [11,12] and landforms [13,14]. For example, Yao et al [15] studied the change in SOM content in different soil depths (0-20, 20-40 and 40-60 cm) in the red soil region of South China, and found that the spatial pattern of SOM was characterized by higher content in the periphery and lower content in the middle.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yao et al [15] studied the change in SOM content in different soil depths (0-20, 20-40 and 40-60 cm) in the red soil region of South China, and found that the spatial pattern of SOM was characterized by higher content in the periphery and lower content in the middle. Zhang et al [14] analyzed the spatial heterogeneity of SOM in the Karst mountain area which possesses a fragile ecology. Their statistical results indicate that the landforms, which lead to great discrepancies in human activities and geographic characteristics, are the primary factor for the high heterogeneity of SOM content in mountainous Karst areas.…”
Section: Introductionmentioning
confidence: 99%